2016
DOI: 10.1590/0103-8478cr20151288
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of several disinfectants against Salmonella enterica serovar Enteritidis and Escherichia coli strains from poultry

Abstract: The efficacy of 28 individual or blended disinfectants against avian Salmonella enterica serovar Enteritidis and Escherichia coli strains was determined. An in vitro test in the presence and absence of serum as source of organic material was conducted. Povidone-iodine (releasing 1% available iodine), 1% potassium permanganate, 70% ethanol, 2% chlorhexidine digluconate and three commercial formulations based on quaternary ammonium compounds + formaldehyde or cresol derivates were the most effective against all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
3
2
0
1
Order By: Relevance
“…The highest MIC level observed here was in the range of levels previously observed in clinical Salmonella Typhimurium (8-16 µg/mL) isolates [55]. But the MIC values for chlorhexidine were lower than many disinfectants, which was in agreement with a study of a S. enterica serovar Enteritidis isolate [52].…”
Section: Disinfectant Susceptibilitysupporting
confidence: 91%
See 1 more Smart Citation
“…The highest MIC level observed here was in the range of levels previously observed in clinical Salmonella Typhimurium (8-16 µg/mL) isolates [55]. But the MIC values for chlorhexidine were lower than many disinfectants, which was in agreement with a study of a S. enterica serovar Enteritidis isolate [52].…”
Section: Disinfectant Susceptibilitysupporting
confidence: 91%
“…But lower levels of formaldehyde or the benzyl compounds were not effective. This is in agreement with a study of a S. enterica serovar Enteritidis field isolate [52]. All 145 Salmonella strains were susceptible to triclosan.…”
Section: Disinfectant Susceptibilitysupporting
confidence: 91%
“…Higher doses should be used. Povidone-iodine, potassium permanganate, ethanol, chlorhexidine digluconate, and hydrogen peroxide exhibited high efficacy in other studies [49,50].…”
Section: Cleaning and Disinfectionmentioning
confidence: 89%
“…Moreover, Kamal et al (2019) showed that some microorganisms as E. coli and Salmonella were able to survive and detected in the environmental samples after disinfection. Results in tables (2-5) revealed that E. coli is the most resistant organism against all the tested disinfectants Martínez-Martínez et al (2016) stated that Virkon-S is not able to inactivate E. coli.…”
Section: Discussionmentioning
confidence: 99%